Ritual Hinting Pali as Resistance of the Dayak Ngaju Community (Case Study of Expansion of Large-Scaled Palm Oil Company to Ecology, Dayak Ngaju Community) - Linggua Sanjaya Usop; Indra Perdana (Britain International for Academic Research (BIAR-Publisher), 2021)
The importance of the ecological and forest conservation of Dayak communities in Central Kalimantan as the support of indigenous communities is not only based on capital and natural resources to meet their needs in the simplest sense, but also in the local philosophy of crisp tree sustainability and balance of God, nature, and human relationships. The global need to meet the market demand for vegetable oil leads to massive expansion of land, environment, and society, especially in developing countries such as Indonesia. This is a debate why these plants can only grow in the tropics, especially in areas passed by the equator. This raises many questions if such expansion attacks in place or region of developed countries like what? how do they handle emerging problems? Regardless of the question, this study only illustrates the contradiction, the idea of the idea of how to protect the environment between local and global values. Hinting pali is a media of Dayak community resistance to ecology and defense disputes related to the existence of the Palm Oil Company [PBS] in Central Kalimantan to the Dayak community. This ritual represents abstinence and prohibition [pali]. This ritual as a message of Dayak community wants to find a win-win solution to conflict and defense dispute between the local community and PBS. The hinting rituals of the Dayak Ngaju community, especially Hindu Kaharingan still grow and develop. Hinting pali as an oral tradition can be used as an effective medium of resistance, especially in conveying their message and protest against ecology and land annihilation by PBS. Hinting pali performance as a Dayak Kaharingan community resistance ritual in Central Kalimantan can express their thoughts and feelings about culture, history, customs, human relationships with the environment and God. They can also use hinting pali to express warnings